Simulasi Numerik Variasi Intake terhadap Karekteristik Aliran pada Basin Turbin Vortex - Andri, Rezky; Yuvenda, Dori; Purwantono, Purwantono (MASALIQ, 2024)
Water has an important role to be used as a source of electrical energy, water is used to drive turbines that will later produce electrical energy, water turbines have great potential to be developed, especially in vortex turbines. A vortex turbine is a turbine that utilizes whirlpool energy to rotate the turbine blades and then convert it into electrical energy. The purpose of this study was to determine the characteristics of the flow in each inflow variation in the vortex turbine basin. The simulation in the study was carried out using solidworks 2023 software using the CFD (Computational Fluid Dynamics) method. After running simulations, velocity data were obtained on each Outer Wall Tangential inflow design of 0.496 m/s, Involute of 0.517 m/s, Ramped Entry of Scrolled Evolute of 0.0857 m/s, and Involute Ramp of 0.551 m/s. pressure in each Outer Wall Tangential inflow design of 100,793.39 N/, Involute of 99,400.12 N/, Ramped Entry of Scrolled Evolute of 99,270.4 N/, and Involute Ramp of 99,324.31 N/. From the simulation results, it can be seen that the largest velocity is obtained in the Ramped Entry of Scrolled Evolute design, and the largest pressure is obtained in the Outer Wall Tangential design.